Activité Anti-Hyperglycémiante Et Élucidation Structurale Des Composés Isolés Des Feuilles De Spondias Purpurea L. (Anacardiaceae) - Diatta, Armel; Manga, Anastasie; Gassama, Abdoulaye; Lavaud, Catherine (European Scientific Journal, ESJ, 2017)
Spondias purpurea L. (Anacardiaceae) is a Senegalese traditional pharmacopoeia plant, which leaves are used in the treatment of various diseases. The leaves’ ethanolic extract exhibited antihyperglycemic activity on models of temporary hyperglycemia. The tests were performed on normoglycemic rats with a glucose tolerance test. The phytochemical investigation of the leaves resulted in the isolation of four flavonoids (quercetin 9, kaempferol 10, quercetin-3- ß-glucopyranoside 6, kaempferol3-ß-galactopyranoside 8), five phenolic compounds (2,4-dihydroxybenzoic acid 2, 4-hydroxybenzoic acid 5, protocatechic 4-ß-glucoside acid 1, hydroxycynnamic acid 7, 5-caffeoylquinic acid 3) and one tannin (Strictinin 4). The known isolated compounds were characterized by NMR and massspectrometry. The present study constitutes the first phytochemical examination of the leaves and the anti-hyperglycemic activity of the ethanolic extract of Spondias Purpurea L.